Association between graduates' factors and success rate on the Saudi Pharmacist Licensure Examination: A single-Institution cross-sectional study - Abdullah A. Alhifany; Faisal A. Almalki; Yasser M. Alatawi; Linah A. Basindowh; Shefaa S. Almajnoni; Mahmoud E Elrggal; Amal F. Alotaibi; Safa S. Almarzoky Abuhussain; Thamer A. Almangour (Elsevier, 2020)
Introduction: The Saudi Pharmacists Licensure Examination's (SPLE) initial results were revealed in February 2020, which showed enormous inconsistency with the passing rates. Hence, we aimed to investigate the predictors of pharmacy graduates' success rate on the SPLE of a single-college in Saudi Arabia. Methods: In a cross-sectional study of 2019-graduates, data were collected via-phone interviews and retrieved from the college's database. Graduates' data were retrieved from the college's database, which includes high school grade point average (GPA), General Aptitude Test, Scholastic Achievement Admission Test, preparatory year GPA, pharmacy GPA, and all courses' grades. The data collected via-phone interview includes information that was not recorded in the college's database, such as date of birth, SPLE score, and the number of SPLE attempts. We only included students who agreed to be interviewed and had attempted the SPLE at least once. We developed a prediction model using correlational analyses and stepwise multiple linear regression to examine graduates' factors in predicting success on the SPLE. Results: Out of the 149 graduates, 105 fulfilled the inclusion criteria. Around 84% of them passed the SPLE. Correlation analyses showed a significant direct correlation between preparatory year GPA and pharmacy GPA with SPLE scores (r = 0.228, P = 0.0193 and r = 0.533, P < 0.0001, respectively). In addition, the results showed that all of the four SPLE content areas were positively correlated with SPLE scores (P < 0.0001). The stepwise multivariable regression showed that being a male graduate and scoring high-grade points in pharmacology and therapeutics courses were significantly associated with high SPLE scores (P = 0.0053, P = 0.0256, and P = 0.0001, respectively). Conclusion: This single cross-sectional study found that being a male, pharmacology GPA, and therapeutics GPA were significantly associated with a higher SPLE score. Further studies should focus on the GPA cut off below which we should give remediation to improve SPLE passing rate.